Spatial distribution of stone crusher units (SCUs) in Sonbhadra district: A geographical perspective - Shailesh Kumar,; Govind Narayan Srivastava,; Anand Prasad Mishra, (National Geographical Journal of India, 2024)
Indian expanding economy, recently experienced many changes in its pattern and nature of development. The increasing space of road, housing and other infrastructural construction increased demand rapidly for stone and its related items. The neo-liberal economy needs more Gross domestic product (G.D.P.) growth and up to $ 5 trillion on the role model for contemporary development. On the base of these more and more crushing industry came in existence. The production of crushed stone in various sizes according to demand, which is used as the raw material for various construction activities such as the building of roads, highways, bridges, buildings, canals, etc., is a significant industrial sector in the nation. This articles explores the spatial distribution of Stone Crushers Units (SCUs) in Sonbhadra district. Owing to lacuna in policy frame works for stone crushing activities, it posed serious challenges for space and society. Owing to ignorance in policies framework the developmental agencies failed to produce reliable data on consequences made by stone crushers in this area. In context to this the present work is an attempt to develop reliable data and its analysis related to peoples, health and spatial environment.